2021
DOI: 10.1111/sjpe.12271
|View full text |Cite
|
Sign up to set email alerts
|

The micro‐geography of academic research: How distinctive is economics?

Abstract: This study examines micro‐geographic clustering in the production and recognition of academic research. Three U.S. ZIP codes are associated with over 40 percent of articles in the top five economics journals and those articles garnered one‐half of all citations in these journals from 2000 to 2015. Such micro‐geographic concentration is not apparent in other disciplines, even those like chemistry that rely on specialized laboratories. Concentration of citations to economics articles whose authors are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…That these simultaneously reinforcing relationships shape institutional hierarchies becomes especially clear when thinking about the close interconnections between specific economics departments with great visibility and prestige (most prominently: Harvard, Chicago and the MIT; see also Medoff (2006)), the discipline's major outlets (like QJE, AER or Econometrica) and the important role US-based PhD programs play for the education of economic research professionals. Thus, by analyzing these relations in greater depth we indeed find that important authors, contributions, departments, and outlets are strongly concentrated in terms of their spatial distribution (Gibson, 2021), their personal as well as professional networks (Colussi, 2018) as well as their biography (e.g. shared PhD-granting institutions).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…That these simultaneously reinforcing relationships shape institutional hierarchies becomes especially clear when thinking about the close interconnections between specific economics departments with great visibility and prestige (most prominently: Harvard, Chicago and the MIT; see also Medoff (2006)), the discipline's major outlets (like QJE, AER or Econometrica) and the important role US-based PhD programs play for the education of economic research professionals. Thus, by analyzing these relations in greater depth we indeed find that important authors, contributions, departments, and outlets are strongly concentrated in terms of their spatial distribution (Gibson, 2021), their personal as well as professional networks (Colussi, 2018) as well as their biography (e.g. shared PhD-granting institutions).…”
Section: Introductionmentioning
confidence: 82%
“…For conducting our empirical investigation, we employ three main sources of bibliographic and biographic data namely (a) Clarivate's annually published journal rankings labeled as Journal Citation Reports (JCR), (b) EconLit as a core database on academic contributions in economics and (c) geographic clusters (together with Chicago and Stanford) represent articles that receive more than the half (55%) of all citations to articles in the top 5 journals (Gibson 2021). manually collected information on the authors in our sample found on CVs and professional websites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a well-defined ranking of journals, with the 'Top Five' dominating all other publications (see the chapter by Heckman and Moktan in this eBook), and a strong concentration of economists from top departments in the leadership of its most important professional association. 3 Gibson (2018) studies the micro-geography of academic research and finds that the concentration of Top Five journals citations in the top three zip codes is much higher in economics than in other fields. In economics, the top three zip codes capture 20% of citations (when NBER affiliations are included in the data, this share increases to 30%) while in sociology, psychology, marketing, philosophy, and chemistry the top three zip codes capture between 7% and 12% of total citations.…”
Section: The Superiority Of Economicsmentioning
confidence: 99%